Pengembangan Sistem Pengamanan Jaringan Komputer Berdasarkan Analisis Forensik Jaringan (Studi Kasus : SMK Putra Anda Binjai) - Yuda Washita; Akim MH Pardede; Husnul Khair (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
The server is something that needs more attention regarding the level of security. Servers that have vulnerabilities can be exploited by irresponsible parties. Data that should be personal can be misused by irresponsible parties. The administrator must ensure that the system is completely secure. One way to maintain server security is by detecting intrusions that are considered dangerous using the Intrusion Detection System (IDS). The intrusion detection system is built based on rules that have been stored in a database (signature-based). Snort is a software that functions to detect intrusions. Data packets passing through network traffic will be analyzed first. Data packets detected as intrusions will trigger an alert which is then stored in a log file. That way, administrators can find out what intrusions occur on the server. However, the administrator needs to analyze on the server computer. The existence of instant messaging applications can help administrators to get notifications in real time. One of them is using Telegram where administrators get brief information and documentation reports of intrusions on the server. Detected intrusions are not only stored in a log file, but can be viewed on the mobile interface via telegram notifications. By implementing IDS, the system can provide real time notifications through instant messaging applications as a solution to facilitate administrators in preventing attacks on the server so that the server remains protected from intrusion by irresponsible parties.